The Supreme Court the personalities and rivalries that defined America - Rosen, Jeffrey 1964- (Times Books, 2007)
"The Supreme Court is the most mysterious branch of government, and yet it is at root a human institution, made up of very bright people with very strong egos, for whom political and judicial conflicts often become personal. In this character-driven history, Rosen recounts the history of the Court through the personal and philosophical rivalries on the bench that transformed the law--and by extension, our lives. Through these four rivalries, he brings to life the perennial conflict that has animated the Court--between those justices guided by strong ideology and those who forge coalitions and adjust to new realities.--From publisher description. Companion to the PBS series."--From source other than the Library of Congress